Strengthening capacities for disaster risk management II: Lessons for effective support. (December 2016) - Few, Roger; Scott, Zoe; Wooster, Kelly; Avila, Mireille Flores; Tarazona, Marcela
Abstract: Across the world there are many initiatives and interventions taking place that directly or indirectly contribute to strengthening capacity for DRM. This paper discusses findings from a 2-year research project on DRM capacity development in lower and middle income countries. The research team undertook case studies of 13 recent or ongoing initiatives across six countries, complemented with an international survey of DRM practitioners. The paper therefore draws lessons from a range of different types of programme to explore the progress being made on the ground toward enhanced capacity development and identify a framework of principles that can serve to underpin effective support in this field. The findings coalesce around concerns related to issues of adaptability, ownership and sustainability, inclusion of actors and scales, the functional scope of capacity development, and the extent to which programmes reflect the wider aspects of DRR. These are factors that ultimately may either derail the success of initiatives, or, when positively addressed, may facilitate the achievement of long-term capacity gains.